May her likes be multiplied : biography and gender politics in Egypt - Booth, Marilyn (University of California Press, 2001)
This study explores the Arabic tradition of life-writing in Egypt. It examines biographical works by women and uses examples of "famous women" biographies - including Joan of Arc and Jane Austen - to demonstrate how these narratives prescribed complex role models for middle-class girls